The Impact of Artificial Intelligence on Workforce Development and the Effectiveness of Decision-Making in the Ministry of Digital Economy and Entrepreneurship in Jordan - Al-Kloub, Mohamed; Awad, Hussein (Ahliya Journal of Business Technology and MEAN Economies, 2024)
The study aimed to explore the impact of artificial intelligence, with its dimensions (neural networks, algorithms, and intelligent agents), on workforce development (employee skills and abilities, training, and incentives) and the effectiveness of decision-making (problem identification, best alternative selection) at the Ministry of Digital Economy and Entrepreneurship in Jordan. The descriptive-analytical approach was used, with a questionnaire as the primary tool for data collection. The study's population consisted of all employees at the Ministry, totaling 356 individuals. Using the comprehensive survey method (targeted sampling), all employees were included as the study sample, and 335 valid questionnaires were retrieved for statistical analysis. The study applied means, standard deviations, and multiple regression analysis, with statistical treatments conducted using SPSS software. The findings revealed that artificial intelligence, in its various dimensions, significantly impacted workforce development and decision-making effectiveness at the Ministry. The study recommended maintaining the application of neural networks in solving organizational management problems to aid in process monitoring, and adopting algorithms in production plans to reduce material consumption, thus helping employees accomplish their tasks more efficiently. The originality of the study lies in its focus on examining the influence of artificial intelligence, through its different dimensions, on workforce development and decision-making effectiveness at the Ministry of Digital Economy and Entrepreneurship in Jordan, contributing to enhanced institutional efficiency and achieving positive outcomes in the workplace.